Diagnosis and Innovative Multidisciplinary Management of Hallermann-Streiff Syndrome: 20-Year Follow-Up of a Patient. (November 2018) - Dulong, Anand; Bornert, Fabien; Gros, Catherine Isabelle; Garnier, Jean-Francois; Van Bellinghen, Xavier; Fioretti, Florence; Lutz, Jean-Christophe
Hallermann-Streiff syndrome (HSS) is a rare congenital disorder that mainly affects head and face development. We described the different patterns of the disease throughout the whole growth period and provided innovative treatment steps. Indeed, early genioplasty and dental implantation before growth completion were performed. These steps allowed to improve facial growth and to provide orthodontic anchorage, respectively. Complementary orthognathic surgery achieved satisfactory occlusion and refined aesthetics. We believe such an approach could be considered as a relevant treatment modality to complete multidisciplinary care in patients with HSS.